Dum spiro spero? (Anna Starobiniec, Żywi) - Aleksandra Zywert (Studia Rossica Posnaniensia)
The subject of the analysis is the short story by Anna Starobiniec titled The alive (2005). By using, inter alia, anti-utopia elements, the author analyzes the contemporary problems of mankind, presenting them against the backdrop of the world after “the end of history”, in which the catastrophe opens a completely new chapter in the history of Russia. The main characters are a pair of humanoids living in the posthuman world who are desperately trying to validate their human identity. In terms of the ideological aspect of the work, this raises the need to reformulate the thesis about the essence of humanity and the question about the criterion of the role and place of man in the world. If we assume that what people hope for defines their place in reality, then how to position the robot that hopes to become human? This problem (in the light of scientific progress) is only apparently distant and exotic, and in fact closer than we all think (especially in the moral and ethical dimension). In this context, it can be said that the story by Starobiniec is an important voice in the discussion on the problems of the future of the modern world in relation to the postulates of transhumanism – that considers and even allows for the abandonment of the human in favor of various variants of the posthuman.